The mechanical and thermal design for the MICE focusing solenoid magnet system - Yang, S; Green, M; Barr, G; Bravar, U; Cobb, J; Lau, W; Senanayake, R; White, A; Witte, H (2005)
The focusing solenoids for MICE surround energy absorbers that are used to reduce the transverse momentum of the muon beam that is being cooled within MICE. The focusing solenoids will have a warm-bore diameter of 470 mm. Within this bore is a flask of liquid hydrogen or a room temperature beryllium absorber. The focusing solenoid consists of two coils wound with a copper matrix Nb-Ti conductor originally designed for MRI magnets. The two coils have separate leads, so that they may be operated at the same polarity or at opposite polarity. The focusing magnet is designed so that it can be cooled with a pair of 1.5 W (at 4.2 K) coolers. The MICE cooling channel has three focusing magnets with their absorbers. The three focusing magnets will be hooked together in series for a circuit stored-energy of about 9.0 MJ. Quench protection for the focusing magnets is discussed. This report presents the mechanical and thermal design parameters for this magnet, including the results of unite element calculations of mechanical forces and heat flow in the magnet cold mass. © 2005 IEEE.